A modified bond-based peridynamic model without limitations on elastic properties. (April 2023) - Masoumi, Alireza; Salehi, Manouchehr; Ravandi, Mohammad
Abstract: This study proposes a novel modified bond-based peridynamic model based on bonds' classifications. Bonds are classified as per the equivalent hypothetical local strains into horizontal normal, vertical normal, and shear bonds. While the classical Bond-Based PeriDynamic (BB-PD) only considers the stretch of bonds, the proposed model takes into account all strain components of the bonds. A local imaginary element is considered around each bond to estimate its true strains. Constitutive relations are derived by equating the strain energies of the bonds' deformations to the strain energies of classical continuum mechanics for a generalized combined loading condition. A novel critical stretch criterion and a critical angle criterion are proposed to predict the failure of normal and shear strain bonds, respectively. Moreover, it is demonstrated that, unlike the classical BB-PD, the proposed model imposes no restrictions on the value of Poisson's ratio. The model is validated by analyzing some intact plane stress and plane strain problems subjected to mechanical and thermal loads. In addition, the deformation and damage contours, as well as the corresponding stress-strain responses, are presented and validated for various problems with pre-existing defects using the extended finite element method.